Utilizing Cooperative Integrated Reading and Composition (CIRC) with Mobile Learning to Enhance Students’ Reading Comprehension - Maspa, Maspa; Sunubi, Abd. Haris; Arqam, Arqam; Saepudin, Saepudin; Dalle, H. Ambo (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
Several phenomena related to students' reading comprehension are observed at SMAN 7 Mimika. Many students struggle to grasp the main ideas of texts and often face challenges in interpreting details and drawing conclusions. Limited vocabulary and a lack of effective reading strategies further hinder their ability to understand complex passages. Research objectives: To analyze the impact of using Cooperative Integrated Reading and Composition (CIRC) with Mobile Learning on students' reading comprehension. To identify the challenges encountered by students when applying CIRC with Mobile Learning in reading activities. The research employed mixed-methods approach. The classical approach to categorize mixed methods designs organizes them into two major categories, sequential and concurrent. The number of sample was 19 students of 64 students. The result of research shows the frequency and percentage of students' pre-test of 19 students. As explained, the highest of students classification in students pre-test was in poor classification with 84,2% or as many 16 students. The results of the study demonstrated a significant enhancement in the students' comprehension of written texts following the implementation of the treatment. future studies may investigate long-term impacts of CIRC with mobile learning, compare with other strategies, explore student motivation, examine teacher training, and apply mixed-method approaches for deeper insights.